Hair Loss in Women - Prevent and Manage with Homoeopathy (Homoeopathy for All, 2024)
Generally, humans shed between  50 and 100 single hairs per day.  Hair shedding is part of a natural  balance — some hairs fall out while  others grow in. An interruption in  this balance — when hair falls out  and less hair grows in — causes hair  loss. The medical term for hair loss  is “alopecia.” Hair grows on almost all of your  skin surfaces — not the palms of  your hands, soles of your feet, lips  or eyelids. Light, fine, short hair is  called vellus hair. Terminal hair is  thicker, darker and longer.
Keywords: compromise; menopause; humans